INHIBITION OF ADVANCED GLYCATION END-PRODUCT FORMATION BY QUERCETIN AND CATECHIN: AN ALTERNATIVE THERAPY FOR TREATING DIABETIC COMPLICATIONS - Julius, Angeline; Hopper, Waheeta (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: The objective of this research was to determine early advanced glycation end-product (AGE) inhibition by natural aldose reductase inhibitors (ARIs), quercetin and catechin. Methods: The assay mixture (4 ml) consisted of 2 ml of 50 mM phosphate-buffered saline (pH 7.4), 50 Î¼g/Î¼l bovine serum albumin (BSA), and 2 mM glucose with or without the inhibitor. The test samples were treated with three different concentrations (10 mM, 20 mM, and 40 mM) of quercetin and catechin. High-throughput screening-based assay was adapted to perform the BSA-glucose test to determine the induction of AGE formation and its inhibition by quercetin, and catechin, using the fluorescence of the AGE-BSA sample at excitation and emission wavelengths of 350 and 450 nm. Result: The ARIs, quercetin and catechin inhibited early glycation with an inhibitory concentration value of 15.58 mM and 35.01 mM, respectively. Conclusion: The suppression of AGEs formation by natural inhibitors of aldose reductase would provide an alternative approach to the control of diabetic complications.